High-strength and high-toughness water-resistant gypsum board and preparation method thereof

CN123003243APending Publication Date: 2026-10-30HUBEI UNIV OF TECH +3
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611468549.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-21
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]鉴于背景技术中存在的技术问题,本发明提供了一种高强高韧耐水石膏板材及其制备方法,旨在解决现有石膏板材存在强度低、韧性差及耐水性不足的技术问题

Benefits of technology

(1)本发明提供的高强高韧耐水石膏板材通过文石型纤维状碳酸钙、方解石型颗粒状碳酸钙与高分子聚合物添加剂的多尺度协同作用,在石膏基体内部构建了刚-柔互穿网络复合结构,实现了石膏板材增韧与增强的同步提升;另外,方解石型颗粒状碳酸钙填充了石膏基体内部的毛细孔隙,同时有机高分子聚合物利用成膜特性在颗粒及基体表面形成连续疏水包覆层,两者协同形成了致密防水复合结构,从而同步提升材料的强度、韧性与耐水性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003243A_ABST
    Figure CN123003243A_ABST
Patent Text Reader

Abstract

The application provides a high-strength high-toughness water-resistant gypsum board and a preparation method thereof, and belongs to the technical field of building materials, wherein the high-strength high-toughness water-resistant gypsum board is prepared from building gypsum, micro-nano composite calcium carbonate slurry and high-molecular polymer additives; the mass ratio of the solid in the micro-nano composite calcium carbonate slurry to the building gypsum is (5-15):(85-95); the mass of the high-molecular polymer additives is 1%-5% of the total solid mass of the building gypsum and the micro-nano composite calcium carbonate slurry; and the mass ratio of the fibrous calcium carbonate to the calcite-type granular calcium carbonate in the micro-nano composite calcium carbonate slurry is (20-60):(40-80). The gypsum board is integrally modified in the aspects of toughness, strength and water resistance by utilizing the synergistic effect of calcium carbonates with different morphologies and crystal types and the interface modification function of the high-molecular polymer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building materials technology, specifically to a high-strength, high-toughness, water-resistant gypsum board and its preparation method. Background Technology

[0002] Gypsum board, with its excellent properties such as lightweight, fire resistance, sound insulation, and moisture regulation, has become an indispensable green building material in modern architectural decoration. However, traditional gypsum board has two inherent defects that severely restrict its application: First, the gypsum crystals are arranged in a needle-like or flake-like interlaced pattern with high internal porosity, resulting in typical brittle fracture characteristics, insufficient impact resistance and bending load-bearing capacity, making it prone to damage during transportation, installation, and use; Second, the hydration product of gypsum products, calcium sulfate dihydrate, has a certain degree of water solubility, and its microstructure contains a large number of capillary pores, allowing water to easily penetrate into the grain boundaries, leading to a significant decrease in strength and poor water resistance, making it difficult to use in high-humidity environments such as kitchens and bathrooms.

[0003] To address the aforementioned problems, researchers both domestically and internationally have conducted numerous modification attempts. Chinese patent CN107226668A discloses a high-strength, water-resistant glass fiber reinforced toughened gypsum board and its preparation method. This technology uses α-type hemihydrate gypsum as the main raw material, incorporating glass fiber and undergoing surface modification treatment to reduce the internal porosity of the gypsum board, increase its compressive strength, and improve its waterproof performance. Chinese patent CN120040160A discloses a fiber-reinforced gypsum board and its preparation method, employing longer basalt fibers to provide macroscopic flexural strength and shorter regenerated cellulose fibers to inhibit microcrack propagation. Chinese patent CN119263762A discloses a high-strength, crack-resistant gypsum board and its preparation method. By adding fiber reinforcing materials and polymer modifiers, the gypsum board achieves higher strength, while using various functional raw materials such as natural resins, fire retardants, and moisture-proofing agents to enhance its crack resistance. However, it is difficult to ensure the uniformity of fiber dispersion in the gypsum matrix, the interfacial bonding strength between the fiber and the matrix is ​​insufficient, and the increase in fiber content often leads to a decrease in the workability of the slurry, resulting in a significant bottleneck in the reinforcing effect.

[0004] Therefore, there is an urgent need to develop a novel composite modification method that can synergistically improve the strength, toughness, and water resistance of gypsum boards. Summary of the Invention

[0005] In view of the technical problems existing in the background art, the present invention provides a high-strength, high-toughness, water-resistant gypsum board and its preparation method, aiming to solve the technical problems of low strength, poor toughness and insufficient water resistance of existing gypsum boards.

[0006] In a first aspect, the present invention provides a high-strength, high-toughness, water-resistant gypsum board, the raw materials for which are prepared include building gypsum, micro-nano composite calcium carbonate slurry, and high molecular polymer additives. The mass ratio of solids to building gypsum in the micro-nano composite calcium carbonate slurry is (5~15):(85~95); the mass of the polymer additive is 1%~5% of the total solid mass of the building gypsum and micro-nano composite calcium carbonate slurry. The polymer additives include at least one of the following: aqueous epoxy resin emulsion, polyacrylate emulsion, and styrene-acrylate copolymer emulsion; The mass ratio of calcite-type fibrous calcium carbonate to calcite-type granular calcium carbonate in the micro-nano composite calcium carbonate slurry is (20~60):(40~80).

[0007] Preferably, the building gypsum includes at least one of desulfurized building gypsum and phosphorus building gypsum.

[0008] Preferably, the preparation method of micro-nano composite calcium carbonate slurry includes the following steps: mixing high-calcium solid waste with a crystal form regulator and water, and then wet milling the mixture. During the wet milling process, CO2 gas is simultaneously introduced to carry out a carbonization reaction. The carbonization reaction temperature is 20~60℃, and the carbonization reaction time is 1~5h, to obtain a micro-nano composite calcium carbonate slurry containing a mixture of aragonite-type fibrous calcium carbonate and calcite-type granular calcium carbonate; the crystal form regulator is a magnesium salt.

[0009] Preferably, the crystal form regulator includes at least one of magnesium sulfate and magnesium chloride; the amount of crystal form regulator added is 0.5% to 6% of the mass of high-calcium solid waste.

[0010] Preferably, the wet grinding conditions are as follows: the grinding media are zirconia balls, the ball-to-material mass ratio is (1~3):1, and the solid-to-liquid mass ratio is (0.5~2):1.

[0011] Preferably, the flow rate of CO2 gas is 1~10 L / min.

[0012] Preferably, the high-calcium solid waste includes at least one of steel slag, carbide slag, and high-calcium fly ash, and the CaO content in the high-calcium solid waste is ≥40%.

[0013] Preferably, the aspect ratio of aragonite-type fibrous calcium carbonate is ≥10, and the particle size of calcite-type granular calcium carbonate is 0.1~5μm.

[0014] Secondly, the present invention provides a method for preparing the above-mentioned high-strength, high-toughness, water-resistant gypsum board, comprising the following steps: Micro-nano composite calcium carbonate slurry, building gypsum, and polymer additives are mixed and stirred evenly to obtain gypsum-based mixed slurry; High-strength, high-toughness, and water-resistant gypsum boards are obtained by pouring and curing gypsum-based mixed slurry.

[0015] The preferred curing conditions are: temperature 40~60℃, humidity 50%~70%RH, and curing time 12~24h.

[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The high-strength, high-toughness, and water-resistant gypsum board provided by the present invention constructs a rigid-flexible interpenetrating network composite structure in the gypsum matrix through the multi-scale synergistic effect of aragonite-type fibrous calcium carbonate, calcite-type granular calcium carbonate and polymer additives, thereby achieving simultaneous improvement in toughness and strength of the gypsum board; in addition, calcite-type granular calcium carbonate fills the capillary pores inside the gypsum matrix, while organic polymers utilize film-forming properties to form a continuous hydrophobic coating layer on the particle and matrix surfaces, and the two work together to form a dense waterproof composite structure, thereby simultaneously improving the strength, toughness and water resistance of the material.

[0017] (2) This invention uses high-calcium solid waste as raw material and prepares functional calcium carbonate through mechanical-chemical wet carbonation technology, realizing the high-value utilization of solid waste and achieving significant environmental benefits. Moreover, the process conditions are mild, highly controllable, and the crystal phase ratio is adjustable. The preparation process of this invention is simple, requiring only the one-time addition of composite calcium carbonate and polymer emulsion to building gypsum to simultaneously achieve integrated modification of toughening, strengthening, and water resistance. Attached Figure Description

[0018] Figure 1 The crystal phase composition test results of the composite calcium carbonate in Examples 1-5 of this invention; Figure 2 This is a scanning electron microscope image of the solid phase in the micro / nano composite calcium carbonate slurry in Example 1 of the present invention; Figure 3 This is a scanning electron microscope image of the high-strength, high-toughness, water-resistant gypsum board prepared in Example 1 of the present invention. Detailed Implementation

[0019] The embodiments of the technical solution of the present invention will now be described in detail with reference to the accompanying drawings. These embodiments are merely illustrative of the technical solution of the present invention and are therefore intended to limit the scope of protection of the present invention.

[0020] To address the technical problems of low strength, poor toughness, and insufficient water resistance in existing gypsum boards, this invention provides a high-strength, high-toughness, and water-resistant gypsum board and its preparation method. The invention achieves multi-scale modification of the microstructure of gypsum materials through a synergistic optimization method of strengthening and toughening with carbonized components and flexible coating with organic polymers, thereby preparing a high-strength, high-toughness, and water-resistant gypsum board.

[0021] In a first aspect, embodiments of the present invention provide a high-strength, high-toughness, water-resistant gypsum board, the raw materials for which are prepared include building gypsum, micro-nano composite calcium carbonate slurry, and high molecular polymer additives. The mass ratio of solids to building gypsum in the micro-nano composite calcium carbonate slurry is (5~15):(85~95); the mass of the polymer additive is 1%~5% of the total solid mass of the building gypsum and micro-nano composite calcium carbonate slurry. The polymer additives include at least one of the following: aqueous epoxy resin emulsion, polyacrylate emulsion, and styrene-acrylate copolymer emulsion; The mass ratio of calcite-type fibrous calcium carbonate to calcite-type granular calcium carbonate in the micro-nano composite calcium carbonate slurry is (20~60):(40~80).

[0022] In the technical solution of this invention embodiment, the micro-nano composite calcium carbonate slurry and the polymer additive have a synergistic effect. Among them, the aragonite-type fibrous calcium carbonate has a high aspect ratio and can form a three-dimensional bridging network in the gypsum matrix, effectively inhibiting the occurrence and propagation of microcracks and significantly improving the toughness of the material. The calcite-type granular calcium carbonate can fill the pores between gypsum hydration products, reduce the porosity of the material, and improve the density and strength. At the same time, the polymer additive utilizes its film-forming properties and interfacial chemical bonding to form a continuous, hydrophobic organic coating layer on the surface of calcium carbonate particles and gypsum matrix. On the one hand, it works synergistically with the aragonite-type fibrous calcium carbonate to construct a rigid-flexible interpenetrating network composite structure, effectively overcoming the high brittleness defect of traditional gypsum materials, greatly improving toughness, and promoting stress dispersion. On the other hand, it imparts hydrophobic properties to the material, blocking water from penetrating into the interior. Together with the calcite-type granular calcium carbonate (which fills the capillary pores inside the material), it forms a dense and waterproof composite structure, significantly improving water resistance. The aforementioned rigid-flexible synergistic mechanism jointly constructs a composite structure of "rigid skeleton + flexible connection + dense filling" within the gypsum matrix, achieving simultaneous optimization of strength, toughness, and water resistance.

[0023] Furthermore, in some embodiments, the building gypsum includes at least one of desulfurized building gypsum and phosphorus building gypsum.

[0024] Furthermore, in some embodiments, the preparation method of micro-nano composite calcium carbonate slurry includes the following steps: mixing high-calcium solid waste with a crystal form regulator and water, followed by wet milling; during the wet milling process, CO2 gas is simultaneously introduced to carry out a carbonization reaction; the carbonization reaction temperature is 20~60℃, and the carbonization reaction time is 1~5h, to obtain a micro-nano composite calcium carbonate slurry containing a mixture of aragonite-type fibrous calcium carbonate and calcite-type granular calcium carbonate; the crystal form regulator is a magnesium salt.

[0025] In the technical solution of this invention embodiment, the invention adopts a mechanical-chemical synergistic wet carbonization technology, using high-calcium solid waste as the core raw material. Through the mechanical force of wet grinding, the high-calcium solid waste particles are fully refined, increasing the specific surface area and promoting the uniformity and efficiency of the carbonization reaction. CO2 gas is simultaneously introduced during the wet grinding process to allow the Ca... 2+ CO3 in slurry 2- In-situ reaction generates calcium carbonate, which is then combined with a crystal form regulator for synergistic reaction. The introduction of magnesium ions inhibits the transformation of calcium carbonate crystal nuclei into stable calcite-type calcium carbonate crystals, promotes the stable formation of aragonite-type calcium carbonate in the slurry, and the content of aragonite-type calcium carbonate in the slurry is controlled by changing the dosage of the crystal form regulator. A micro-nano composite calcium carbonate slurry containing a mixture of aragonite-type fibrous calcium carbonate and calcite-type granular calcium carbonate is thus prepared.

[0026] Furthermore, in some embodiments, the crystal form regulator includes at least one of magnesium sulfate and magnesium chloride; the amount of crystal form regulator added is 0.5% to 6% of the mass of the high-calcium solid waste.

[0027] In the technical solution of this invention embodiment, the magnesium ions provided by the crystal form regulator inhibit the transformation of calcium carbonate crystal nuclei into stable calcite-type calcium carbonate crystals, promoting the stable formation of aragonite-type calcium carbonate in the slurry. By controlling the dosage of the crystal form regulator, the content of aragonite-type calcium carbonate in the slurry can be controlled, thereby achieving precise control of the crystal form ratio of micro-nano composite calcium carbonate. When the dosage of the crystal form regulator is less than 0.5%, the magnesium ion concentration is insufficient, the amount of aragonite-type calcium carbonate generated is small, and the strengthening and toughening effect is limited. As the dosage of the crystal form regulator increases, the proportion of aragonite-type calcium carbonate gradually increases, and the strengthening and toughening effect of the material is significantly improved. However, when the proportion of aragonite-type calcium carbonate is too high, the water resistance may decrease due to the increased pore connectivity caused by the fibrous structure. Extensive experiments have shown that controlling the dosage of the crystal form regulator within the range of 0.5% to 6% can achieve a better ratio of aragonite-type and calcite-type calcium carbonate while ensuring normal hydration of gypsum, thus balancing strengthening, toughening, and water resistance.

[0028] Furthermore, in some embodiments, the wet milling conditions are as follows: the grinding media are zirconia balls, the ball-to-material mass ratio is (1~3):1, and the solid-to-liquid mass ratio is (0.5~2):1.

[0029] Furthermore, in some embodiments, the flow rate of CO2 gas is 1~10 L / min.

[0030] Furthermore, in some embodiments, the high-calcium solid waste includes at least one of steel slag, carbide slag, and high-calcium fly ash, and the CaO mass content in the high-calcium solid waste is ≥40%.

[0031] Furthermore, in some embodiments, the aspect ratio of aragonite-type fibrous calcium carbonate is ≥10, and the particle size of calcite-type granular calcium carbonate is 0.1~5μm.

[0032] Furthermore, in some embodiments, the solid content of the polymer additive is 30% to 50%.

[0033] Secondly, embodiments of the present invention provide a method for preparing high-strength, high-toughness, water-resistant gypsum board, comprising the following steps: Micro-nano composite calcium carbonate slurry, building gypsum, and polymer additives are mixed and stirred evenly to obtain gypsum-based mixed slurry; High-strength, high-toughness, and water-resistant gypsum boards are obtained by pouring and curing gypsum-based mixed slurry.

[0034] Furthermore, in some embodiments, the curing conditions are: temperature 40~60℃, humidity 50%~70%RH, and curing time 12~24h.

[0035] The following are some specific embodiments. It should be noted that the embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0036] Example 1 A method for preparing high-strength, high-toughness, water-resistant gypsum board, the specific steps of which are as follows: (1) Steel slag (CaO content 45%), magnesium sulfate, and water were mixed and subjected to wet ball milling. The solid-liquid mass ratio was 1:1, the amount of magnesium sulfate added was 4% of the steel slag mass, the grinding media was zirconia balls, the ball-to-material mass ratio was 2:1, and the ball milling time was 3h. During the wet milling process, CO2 gas with a flow rate of 5 L / min was simultaneously introduced to carry out a carbonization reaction. The carbonization reaction temperature was 40℃, and the reaction time was 3h, resulting in a micro-nano composite calcium carbonate slurry containing a mixture of aragonite-type fibrous calcium carbonate and calcite-type granular calcium carbonate. The crystal phase composition of the composite calcium carbonate was analyzed by XRD characterization, and the results are as follows: Figure 1 As shown, the mass ratio of aragonite-type fibrous calcium carbonate to calcite-type granular calcium carbonate is 35:65 (see...). Figure 1 , Figure 1 (Results of crystal phase composition testing for composite calcium carbonate) Aragonite-type fibrous calcium carbonate has an aspect ratio ≥10, and calcite-type granular calcium carbonate has a particle size of 0.1~5 μm (see... Figure 2 , Figure 2 (Scanning electron microscope image of the solid phase in micro / nano composite calcium carbonate slurry). (2) Mix the micro-nano composite calcium carbonate slurry with desulfurized building gypsum. The solid mass ratio of the micro-nano composite calcium carbonate slurry to the desulfurized building gypsum is 10:90 based on the solid content. At the same time, add water-based epoxy resin emulsion (solid content 40%), the amount of which is 3% of the total solid mass (the total mass of composite calcium carbonate solid and gypsum solid). Mix and stir for 2 minutes. Utilize the film-forming properties and interfacial chemical bonding of the water-based epoxy resin emulsion to form a flexible coating layer on the surface of calcium carbonate particles and gypsum matrix, and obtain a uniform gypsum-based mixed slurry. (3) After the gypsum-based mixed slurry is cast into shape, it is cured for 18 h at a temperature of 50℃ and a humidity of 60% RH to obtain a 10 mm thick high-strength, high-toughness, water-resistant gypsum board.

[0037] Figure 3 Here is a scanning electron microscope image of the high-strength, high-toughness, water-resistant gypsum board prepared in this embodiment, as shown. Figure 3 As shown, this invention constructs a rigid-flexible interpenetrating network composite structure within the gypsum board matrix through the synergistic effect of aragonite-type fibrous calcium carbonate, calcite-type granular calcium carbonate, and water-based epoxy resin.

[0038] Example 2 A method for preparing high-strength, high-toughness, water-resistant gypsum board, the specific steps of which are as follows: (1) Calcium carbide slag (CaO content 50%), magnesium chloride, and water were mixed and subjected to wet ball milling. The solid-liquid mass ratio was 0.5:1, the amount of magnesium chloride added was 6% of the mass of calcium carbide slag, the grinding media was zirconia balls, the ball-to-material mass ratio was 1:1, and the ball milling time was 5h. During the wet milling process, CO2 gas with a flow rate of 10 L / min was simultaneously introduced to carry out a carbonization reaction. The carbonization reaction temperature was 20℃, and the reaction time was 5h, resulting in a micro-nano composite calcium carbonate slurry containing a mixture of aragonite-type fibrous calcium carbonate and calcite-type granular calcium carbonate. XRD characterization analysis showed that the mass ratio of aragonite-type fibrous calcium carbonate to calcite-type granular calcium carbonate was 58:42 (see Figure 1 Aragonite-type fibrous calcium carbonate has an aspect ratio ≥12, while calcite-type granular calcium carbonate has a particle size of 0.1~5 μm. (2) Mix the micro-nano composite calcium carbonate slurry with phosphorus building gypsum. The mass ratio of the solid content of the micro-nano composite calcium carbonate slurry to that of phosphorus building gypsum is 5:95. At the same time, add polyacrylate emulsion (solid content 50%), the amount of which is 5% of the total solid mass (the total mass of composite calcium carbonate solid and gypsum solid). Mix and stir for 3 minutes. Utilize the film-forming properties and interfacial chemical bonding of polyacrylate emulsion to form a flexible coating layer on the surface of calcium carbonate particles and gypsum matrix to obtain a uniform gypsum-based mixed slurry. (3) After the gypsum-based mixed slurry is cast into shape, it is cured for 24 hours at a temperature of 40℃ and a humidity of 50% RH to obtain a 10 mm thick high-strength, high-toughness, water-resistant gypsum board.

[0039] Example 3 A method for preparing high-strength, high-toughness, water-resistant gypsum board, the specific steps of which are as follows: (1) High-calcium fly ash (CaO content 42%), magnesium chloride and water were mixed and subjected to wet ball milling. The solid-liquid mass ratio was 2:1, the amount of magnesium chloride added was 0.5% of the mass of high-calcium fly ash, the grinding media was zirconia balls, the ball-to-material mass ratio was 3:1, and the ball milling time was 1 h. During the wet milling process, CO2 gas with a flow rate of 1 L / min was simultaneously introduced to carry out carbonation reaction. The carbonation reaction temperature was 60℃ and the reaction time was 1 h, resulting in a micro-nano composite calcium carbonate slurry containing a mixture of aragonite-type fibrous calcium carbonate and calcite-type granular calcium carbonate. XRD characterization analysis showed that the mass ratio of aragonite-type fibrous calcium carbonate to calcite-type granular calcium carbonate was 22:78 (see Figure 1 Aragonite-type fibrous calcium carbonate has an aspect ratio ≥10, while calcite-type granular calcium carbonate has a particle size of 0.1~5 μm. (2) Mix the micro-nano composite calcium carbonate slurry with desulfurized building gypsum. The mass ratio of the solid content of the micro-nano composite calcium carbonate slurry to that of the desulfurized building gypsum is 15:85. At the same time, add styrene-acrylate copolymer emulsion (solid content 30%), the amount of which is 1% of the total solid mass (the total mass of composite calcium carbonate solid and gypsum solid). Mix and stir for 1 min. Utilize the film-forming properties and interfacial chemical bonding of the styrene-acrylate copolymer emulsion to form a flexible coating layer on the surface of calcium carbonate particles and gypsum matrix, and obtain a uniform gypsum-based mixed slurry. (3) After the gypsum-based mixed slurry is cast into shape, it is cured for 12 hours at a temperature of 60℃ and a humidity of 70% RH to obtain a 10 mm thick high-strength, high-toughness, water-resistant gypsum board.

[0040] Example 4 A method for preparing high-strength, high-toughness, water-resistant gypsum board, the specific steps of which are as follows: (1) A mixture of high-calcium solid waste (CaO content 48%) consisting of steel slag and carbide slag in a mass ratio of 1:1 was used as raw material. This mixture was then wet-milled with a crystal modifier (a mixture of magnesium sulfate and magnesium chloride in a mass ratio of 1:1) and water. The solid-liquid mass ratio was 1.5:1, and the amount of crystal modifier added was 6% of the mass of the mixed high-calcium solid waste. The grinding media was zirconia balls, with a ball-to-material mass ratio of 2.5:1, and the milling time was 2 hours. During the wet milling process, CO2 gas at a flow rate of 8 L / min was simultaneously introduced for carbonation. The carbonation reaction temperature was 30℃, and the reaction time was 2 hours, resulting in a micro / nano composite calcium carbonate slurry containing a mixture of aragonite-type fibrous calcium carbonate and calcite-type granular calcium carbonate. XRD characterization analysis showed that the mass ratio of aragonite-type fibrous calcium carbonate to calcite-type granular calcium carbonate was 50:50 (see...). Figure 1 Aragonite-type fibrous calcium carbonate has an aspect ratio ≥15, while calcite-type granular calcium carbonate has a particle size of 0.1~5 μm. (2) The micro-nano composite calcium carbonate slurry is mixed with phosphorus building gypsum. The mass ratio of the solid content of the micro-nano composite calcium carbonate slurry to that of phosphorus building gypsum is 8:92. At the same time, water-based epoxy resin emulsion (solid content 45%) is added at a rate of 4% of the total solid mass (the total mass of composite calcium carbonate solid and gypsum solid). The mixture is stirred for 2.5 min. By utilizing the film-forming properties and interfacial chemical bonding of the water-based epoxy resin emulsion, a flexible coating layer is formed on the surface of calcium carbonate particles and gypsum matrix to obtain a uniform gypsum-based mixed slurry. (3) After the gypsum-based mixed slurry is cast into shape, it is cured for 20 hours at a temperature of 55℃ and a humidity of 55% RH to obtain a 10 mm thick high-strength, high-toughness, water-resistant gypsum board.

[0041] Example 5 A method for preparing high-strength, high-toughness, water-resistant gypsum board, the specific steps of which are as follows: (1) A mixture of high-calcium solid waste (CaO content 46%) consisting of carbide slag and high-calcium fly ash in a mass ratio of 2:1 was used as raw material. This mixture was then wet-milled with a crystal modifier (a mixture of magnesium chloride and magnesium sulfate in a mass ratio of 2:1) and water. The solid-liquid mass ratio was 0.8:1, and the amount of crystal modifier added was 2% of the mass of the mixed high-calcium solid waste. The grinding media was zirconia balls, with a ball-to-material mass ratio of 1.5:1, and the milling time was 4 hours. During the wet milling process, CO2 gas at a flow rate of 3 L / min was simultaneously introduced for carbonation. The carbonation reaction temperature was 30℃, and the reaction time was 4 hours, resulting in a micro / nano composite calcium carbonate slurry containing a mixture of aragonite-type fibrous calcium carbonate and calcite-type granular calcium carbonate. XRD characterization analysis showed that the mass ratio of aragonite-type fibrous calcium carbonate to calcite-type granular calcium carbonate was 30:70 (see...). Figure 1Aragonite-type fibrous calcium carbonate has an aspect ratio ≥10, while calcite-type granular calcium carbonate has a particle size of 0.1~5 μm. (2) The micro-nano composite calcium carbonate slurry is mixed with desulfurized building gypsum. The mass ratio of the solid content of the micro-nano composite calcium carbonate slurry to that of the desulfurized building gypsum is 12:88. At the same time, polyacrylate emulsion (solid content 35%) is added at a rate of 2% of the total solid mass (the total mass of composite calcium carbonate solid and gypsum solid). The mixture is stirred for 2 minutes. By utilizing the film-forming properties and interfacial chemical bonding of the polyacrylate emulsion, a flexible coating layer is formed on the surface of the calcium carbonate particles and the gypsum matrix to obtain a uniform gypsum-based mixed slurry. (3) After the gypsum-based mixed slurry is cast into shape, it is cured for 16 hours at a temperature of 45℃ and a humidity of 65% RH to obtain a 10 mm thick high-strength, high-toughness, water-resistant gypsum board.

[0042] Comparative Example 1 The difference between this comparative example and Example 1 is that the composite calcium carbonate slurry is replaced with commercially available single calcite crystal calcium carbonate. The specific steps are as follows: (1) Purchased calcite-type calcium carbonate (particle size 0.1~5μm) is mixed with desulfurized building gypsum. The mass ratio of calcite-type calcium carbonate to desulfurized building gypsum is 10:90. At the same time, water-based epoxy resin emulsion (solid content 40%) is added. The amount added is 3% of the total solid mass (the total mass of calcium carbonate solid and gypsum solid). The mixture is stirred for 2 min to obtain gypsum-based mixed slurry. (2) After the gypsum-based mixed slurry is poured into shape, it is cured for 18 h at a temperature of 50℃ and a humidity of 60% RH to obtain a 10 mm thick gypsum board.

[0043] Comparative Example 2 The difference between this comparative example and Example 1 is that the composite calcium carbonate slurry is replaced with calcium carbonate of the single calcite crystal form and glass fiber. The specific steps are as follows: (1) Purchased calcite-type calcium carbonate (particle size 0.1~5μm) and glass fiber (length-to-diameter ratio 10) are mixed at a mass ratio of 65:35. The mixture of calcium carbonate and glass fiber is mixed with desulfurized building gypsum. The mass ratio of the mixture of calcium carbonate and glass fiber to desulfurized building gypsum is 10:90. At the same time, water-based epoxy resin emulsion (solid content 40%) is added at a mass of 3% of the total solid mass (the total mass of calcium carbonate, glass fiber and gypsum solids). The mixture is stirred for 2 min to obtain gypsum-based mixed slurry. (2) After the gypsum-based mixed slurry is poured into shape, it is cured for 18 h at a temperature of 50℃ and a humidity of 60% RH to obtain a 10 mm thick gypsum board.

[0044] Comparative Example 3 The difference between this comparative example and Example 1 is that no aqueous epoxy resin emulsion is added. The specific steps are as follows: (1) Same as step (1) in Example 1; (2) Mix the micro-nano composite calcium carbonate slurry with desulfurized building gypsum. The solid content of the micro-nano composite calcium carbonate slurry is 10:90 in mass ratio with the desulfurized building gypsum. Add water only to adjust to the same fluidity as in Example 1. Mix and stir for 2 min to obtain gypsum-based mixed slurry. (2) After the gypsum-based mixed slurry is poured into shape, it is cured for 18 h at a temperature of 50℃ and a humidity of 60% RH to obtain a 10 mm thick gypsum board.

[0045] Comparative Example 4 This comparative example is a traditional unmodified desulfurized building gypsum board, which is prepared by mixing desulfurized building gypsum and water at a water-to-gypsum ratio of 1:0.65. The gypsum board is 10 mm thick and is prepared under the same molding and curing conditions as in Example 1 (50°C, 60% RH, 18 h).

[0046] Performance Testing and Results Analysis Mechanical properties and water resistance were tested on the gypsum boards prepared in Examples 1-5 and Comparative Examples 1-4. The main test items included: breaking load, shear force, water absorption thickness expansion rate and softening coefficient. The breaking load was tested according to the method specified in GB / T 9775-2025, and the average breaking load was the average of the test results of 5 specimens. Shear force was tested according to the method specified in GB / T 9775-2025, and the average value of the test results of 5 specimens was taken. The water absorption thickness swelling rate was tested according to the method specified in GB / T 17657-2013, and the thickness change rate was measured after soaking in water at 20℃ for 24 hours. The softening coefficient was tested according to the method specified in JC / T 698-2010. The specimen was soaked in water at 20℃ for 24 hours, and the ratio of the fracture load before and after immersion was taken.

[0047] The test results are shown in Table 1.

[0048] Table 1

[0049] Table 1 shows that the gypsum board prepared in the embodiments of the present invention is significantly superior to the comparative examples in key performance indicators such as fracture load, shear force, water absorption thickness expansion rate, and softening coefficient, exhibiting high strength, high toughness, and good water resistance. The present invention, through the synergy of aragonite-type fibrous calcium carbonate and organic polymer, constructs a rigid-flexible interpenetrating network composite structure within the gypsum matrix, overcoming the high brittleness defect of traditional gypsum materials. Furthermore, calcite-type granular calcium carbonate fills the pores within the gypsum matrix, aragonite-type fibrous calcium carbonate bridges microcracks in the gypsum matrix, organic polymer disperses the stress on the matrix, and the organic polymer utilizes its film-forming properties to form a continuous hydrophobic coating layer on the particle and matrix surfaces, forming a dense, waterproof composite structure. Ultimately, this achieves integrated modification of the gypsum board in terms of reinforcement, toughening, and water resistance.

[0050] Comparative Example 1 uses only calcite-type calcium carbonate, lacking the bridging and toughening effect of aragonite-type fibrous calcium carbonate, resulting in insufficient internal density of the material and a decrease in the mechanical properties and water resistance of the gypsum board.

[0051] Although glass fiber was introduced in Comparative Example 2 in an attempt to improve toughness, the overall performance improvement was limited due to the poor interfacial compatibility between glass fiber and gypsum matrix.

[0052] In Comparative Example 3, which did not contain waterborne epoxy resin emulsion, although the composite calcium carbonate could improve the reinforcing effect to a certain extent, the water resistance was significantly weakened because it could not effectively disperse stress due to the absence of organic polymer and the lack of a continuous hydrophobic coating layer on the particle and matrix surfaces.

[0053] It should be noted that the present invention is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments that have the same structure and perform the same effects as the technical concept within the scope of the present invention are included within the scope of the present invention. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of the present invention, are also included within the scope of the present invention.

Claims

1. A high-strength, high-toughness, water-resistant gypsum board, characterized in that, The raw materials for preparation include building gypsum, micro-nano composite calcium carbonate slurry, and polymer additives; The mass ratio of solids in the micro-nano composite calcium carbonate slurry to the building gypsum is (5~15):(85~95); the mass of the polymer additive is 1%~5% of the total solid mass of the building gypsum and the micro-nano composite calcium carbonate slurry. The polymer additives include at least one of aqueous epoxy resin emulsion, polyacrylate emulsion, and styrene-acrylate copolymer emulsion; The mass ratio of calcite-type fibrous calcium carbonate to calcite-type granular calcium carbonate in the micro-nano composite calcium carbonate slurry is (20~60):(40~80).

2. The high-strength, high-toughness, water-resistant gypsum board according to claim 1, characterized in that, The building gypsum includes at least one of desulfurized building gypsum and phosphorus building gypsum.

3. The high-strength, high-toughness, water-resistant gypsum board according to claim 1, characterized in that, The preparation method of the micro / nano composite calcium carbonate slurry includes the following steps: High-calcium solid waste is mixed with a crystal form regulator and water and then wet-milled. During the wet milling process, CO2 gas is simultaneously introduced to carry out a carbonation reaction. The carbonation reaction temperature is 20~60℃ and the carbonation reaction time is 1~5h, resulting in a micro-nano composite calcium carbonate slurry containing a mixture of aragonite-type fibrous calcium carbonate and calcite-type granular calcium carbonate. The crystal form regulator is a magnesium salt.

4. The high-strength, high-toughness, water-resistant gypsum board according to claim 3, characterized in that, The crystal form regulator includes at least one of magnesium sulfate and magnesium chloride; And / or, the amount of the crystal form regulator added is 0.5% to 6% of the mass of the high-calcium solid waste.

5. A high-strength, high-toughness, water-resistant gypsum board according to claim 3, characterized in that, The conditions for wet grinding are as follows: the grinding media is zirconia balls, the ball-to-material mass ratio is (1~3):1, and the solid-to-liquid mass ratio is (0.5~2):

1.

6. The high-strength, high-toughness, water-resistant gypsum board according to claim 3, characterized in that, The flow rate of the CO2 gas is 1~10 L / min.

7. A high-strength, high-toughness, water-resistant gypsum board according to claim 3, characterized in that, The high-calcium solid waste includes at least one of steel slag, carbide slag, and high-calcium fly ash, and the CaO content in the high-calcium solid waste is ≥40%.

8. The high-strength, high-toughness, water-resistant gypsum board according to claim 1, characterized in that, The aragonite-type fibrous calcium carbonate has an aspect ratio ≥10, and the calcite-type granular calcium carbonate has a particle size of 0.1~5μm.

9. The method for preparing high-strength, high-toughness, water-resistant gypsum board as described in any one of claims 1 to 8, characterized in that, Micro-nano composite calcium carbonate slurry, building gypsum, and polymer additives are mixed and stirred evenly to obtain gypsum-based mixed slurry; The gypsum-based mixed slurry is poured into molds and cured to obtain high-strength, high-toughness, and water-resistant gypsum boards.

10. The method for preparing a high-strength, high-toughness, water-resistant gypsum board according to claim 9, characterized in that, The curing conditions are: temperature 40~60℃, humidity 50%~70%RH, and curing time 12~24h.

Citation Information

Patent Citations

  • High-strength water-resistant glass-fiber-reinforced / toughened gypsum board and preparation method thereof

    CN107226668A

  • High-strength anti-cracking gypsum board and preparation method thereof

    CN119263762A

  • Fiber reinforced gypsum board and preparation method thereof

    CN120040160A